Techno-economic analysis of heat pumping technology for oleochemical fatty acid fractionation - Norul Malakiah, Sidek; Mohamad Rizza, Othman (Elsevier B.V., 2020)
Distillation unit is often known as a major energy consumer in chemical refineries. Recent researches have shown an increased interest in heat pumping technology. So far, previous studies of heat pump integrated column have not dealt with industrial oleochemical separation. The aim of this research paper has therefore been to investigate the implications of using heat pumping technology on oleochemical fractionation. This work takes the form of an industrial case-study of palm kernel oil (PKO) fatty acid fractional distillation. Two different arrangements of mechanical vapour recompression (MVR); namely direct vapour recompression (VRC) and bottom flashing heat pump (BFHP), were introduced to the process and their performances were assessed for technological efficacy as well as cost effectiveness. All simulations were carried out using Aspen Plus process simulator and UNIQUAC was chosen as the most suitable thermodynamic package. Economic analysis in terms of capital expenses (CAPEX) and operational expenses (OPEX) was evaluated. Though both MVR systems have shown relative reduction in energy load, however the CAPEX performance demonstrated in this study was not very appealing due to the additional equipment to satisfy the energy requirement. One anticipated finding was that the OPEX for the VRC showed only 50% from the conventional column (CC). On the contrary, the BFHP was ruled out for its CAPEX and OPEX, which showed twice as much as the CC.